The Balance of Theoretical and Practical Skills in Agricultural Technical Schools in Haiti: An Exploration of the Curriculum - Christelle M. Calixte; Grady T. Roberts; J. C. Bunch (Journal of International Agricultural and Extension Education, 2019)
Haiti, with its alarming hunger index, and serious concerns for the population’s food security status, suggests that its agricultural production and productivity are insufficient to guarantee availability of food for the people. Increased productivity supposes the dissemination of best agricultural practices among farmers, and enough qualified extension agents carrying the scientific findings into the rural communities. However, studies in Haiti, have found that the extension activities are mostly conducted by graduates from TVET schools. Meanwhile, little is known about the quality of the training provided in these institutions. This study explored the balance of practice and theory in Haitian TVET curricula. Individual interviews to directors and teachers and focus groups with students explained the role of practical experiences in TVET curriculum by emphasizing on the importance, the purposes and the amount of such practical experiences in the program of study. The various instructional methods used to ensure sufficient practices were also revealed, specifically, participative methods, research and various field activities. Nevertheless, many barriers impede more practices, which were (a) scheduling, (b) lack of resources, (c) students’ attitudes, (d) absence of laboratories in Haiti, and (e) the rural reality and environmental issues.
Keywords: Haiti; experiential learning; technical schools; agriculture